Emily Dickinson : A Literary Life - Wagner-Martin, Linda (Basingstoke Palgrave Macmillan, 2015)
Now published in paperback for the first time, this literary biographical study charts Dickinson's hard-won brilliance as she worked, largely alone, to become the unique American woman writer of the nineteenth century.
Include Index and Bibliography
Keywords: Women poets, American